Treatment of Lymphatic Filariasis with Wolbachia Targets - Inneke Kusumawati Susanto (Jurnal MedScientiae, 2022)
Nematodes are the cause of filariasis. Tissue nematodes as the cause of lymphatic filariasis are 3 species, namely Wuchereria bancrofti, Brugia malayi, Brugia timori.1 Lymphatic filariasis is the second largest cause of long-term disability, namely lymphedema of the extremities (elephantiasis) and hydrocele, especially in the tropics.2 Wolbachia bacteria are found in Onchocercidae, the family of filarial nematodes, including species that cause filarial disease in humans such as lymphatic filariasis and onchocerciasis. The symbiosis of Wolbachia and Onchocercidae shows that Wolbachia bacteria play a role in the treatment of filarial parasitic infections by using antibiotics such as tetracycline, doxycycline or rifampicin causing growth retardation and embryogenesis. 4 The long term use of antibiotics is feared to cause resistance to bacteria. Therefore, it is necessary to use antibiotics with a shorter time.